A Prior Magazine 16. - Szewczyk, Monika; Aguirre, Peio; Cope, Louise; Kreuger, Anders; Lauwaert, Maaike; De Preester, Frederik; Roelandt, Els; Van Bogaert, Pieter; Wiarda, Andrea (Ghent : Kask,vzw Mark, 2008)
De Clercq, Anouk ; Philipsz, Susan ; Martens, Renzo ; Toufic, Jalal ; Ziura, Darius
boek